Jurisprudential and Legal Review of Restricting Expressional Entertainment - mahmood hekmatnia; Davood Khoshnevis (پژوهش تطبیقی حقوق اسلام و غرب, 2020)
Expressional entertainment as a specific type of expression, which include message and content are entertaining and in different formats, can be subject to legal and jurisprudential analysis, and according to their legitimacy, they are subject to the rule governing the expression e.g. freedom. From this perspective, your expressive entertainment, regardless of content and format, is considered as a value. But due to the social nature of the statement and the impact of its content on the audience, the freedom of expression is limited by the grounds of its legitimacy and the basis of restriction. Non-harm, interference with the rights of others, public order are among the most important legal and jurisprudential grounds of restricting the content of entertainment, which sometimes excludes content from the scope of the expression and sometimes by way of a ruling and by applying certain rules based on the foundations limits the content. On the other hand, the effects of expression, including the time, place, and manner appropriate to the audience in delivering the content, can be restricted on the basis of the foundation. The Iranian legislator has taken a preventive and generally ambiguous view of content restriction, which can be prevented by limiting the scope of content with these titles in the Intellectual Property Protection Bill. The present study is aimed at achievement of the said goal through a descriptive-analytic method.